Racialized geographies of home: Property, unhoming and other possible futures. (August 2022) - Nethercote, Megan
This article interrogates the racial logics of home and homemaking. It opens up the conceptual terrain of home to property – a technology of racial dispossession and handmaid of racial capitalism. I reconceptualize home as dominion and as belonging. Unhoming names the synergies between these modalities that authorizes the unmaking of racialized subjects' homes. I argue unhoming is a structural feature of racial capitalism and position resistance to unhoming as homemaking that might rescript propertied landscapes. Repositioning home as practised in propertied landscapes centres homemaking's life-giving and death-dealing contradictions and excavates the work home does for – and (might do) to disrupt – liberal property regimes.